2022
DOI: 10.1101/mcs.a006180
|View full text |Cite
|
Sign up to set email alerts
|

Inherited and de novo variants extend the etiology of TAOK1-associated neurodevelopmental disorder

Abstract: Alterations in the TAOK1 gene have recently emerged as the cause of developmental delay with or without intellectual impairment or behavioral abnormalities (MIM #619575). The thirty-two cases currently described in the literature have predominantly de novo alterations in TAOK1 and a wide spectrum of neurodevelopmental abnormalities. Here, we report four patients with novel pathogenic TAOK1 variants identified by research genome sequencing, clinical exome sequencing, and international matchmaking. The overlappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…To the best of our knowledge, only six studies have reported variants of TAOK1 in 40 patients with NDDs ( Xie et al, 2016 ; Dulovic-Mahlow et al, 2019 ; Satterstrom et al, 2020 ; Basel-Salmon et al, 2021 ; van Woerden et al, 2021 ; Hunter et al, 2022 ). The phenotypes of the affected individuals are summarized in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, only six studies have reported variants of TAOK1 in 40 patients with NDDs ( Xie et al, 2016 ; Dulovic-Mahlow et al, 2019 ; Satterstrom et al, 2020 ; Basel-Salmon et al, 2021 ; van Woerden et al, 2021 ; Hunter et al, 2022 ). The phenotypes of the affected individuals are summarized in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Variants in five (12.5%) affected individuals, P8, P9, P23, P37, and P38, were considered to be inherited from an affected mother or father ( Table 1 ), which are classified as pathogenic herein. The very mild cognitive phenotypes of some affected parents might be explained by incomplete penetrance and variable expressivity ( Hunter et al, 2022 ). Furthermore, no recurrent variants were reported in the region of 17q11.2 (chr17: 27064286-28761847), indicating that TAOK1 is not prone to hotspot variant, which was also mentioned by van Woerden et al (2021) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thousand and one amino acid kinase 1 (TAOK1) is an evolutionarily conserved serine-threonine kinase (Moore et al, 2000; Zihni et al, 2006). Recently, several missense and truncation mutations in TAOK1 have been recently identified in patients with severe neurodevelopmental delay (NDD) (Dulovic-Mahlow et al, 2019; Hunter et al, 2022; Satterstrom et al, 2020; Woerden et al, 2021). The core clinical features of patients with TAOK1-associated NDD syndrome include varying degrees of intellectual disability and developmental delay, neonatal feeding difficulties, overlapping dysmorphic facial features, behavior problems, hypotonia, and joint hypermobility (Dulovic-Mahlow et al, 2019; Hunter et al, 2022; Woerden et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several missense and truncation mutations in TAOK1 have been recently identified in patients with severe neurodevelopmental delay (NDD) (Dulovic-Mahlow et al, 2019; Hunter et al, 2022; Satterstrom et al, 2020; Woerden et al, 2021). The core clinical features of patients with TAOK1-associated NDD syndrome include varying degrees of intellectual disability and developmental delay, neonatal feeding difficulties, overlapping dysmorphic facial features, behavior problems, hypotonia, and joint hypermobility (Dulovic-Mahlow et al, 2019; Hunter et al, 2022; Woerden et al, 2021). While evidence for the disease association of TAOK1 is compelling, little is known about the molecular and cellular function of TAOK1 in neuronal development.…”
Section: Introductionmentioning
confidence: 99%